2022
DOI: 10.3390/ani12192702
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining as a Tool to Infer Chicken Carcass and Meat Cut Quality from Autochthonous Genotypes

Abstract: The present research aims to develop a carcass quality characterization methodology for minority chicken populations. The clustering patterns described across local chicken genotypes by the meat cuts from the carcass were evaluated via a comprehensive meta-analysis of ninety-one research documents published over the last 20 years. These documents characterized the meat quality of native chicken breeds. After the evaluation of their contents, thirty-nine variables were identified. Variables were sorted into eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 159 publications
(89 reference statements)
0
9
0
Order By: Relevance
“…Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were designed for the healthcare field and do not fit properly in livestock research ( 39 , 40 ). Furthermore, strict adherence to the PRISMA guidelines failed to detect any alterations in the journal’s level of recommendation and endorsement ( 41 ) and exhibited restricted suitability in the context of reviews concerning conservation and environmental management.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were designed for the healthcare field and do not fit properly in livestock research ( 39 , 40 ). Furthermore, strict adherence to the PRISMA guidelines failed to detect any alterations in the journal’s level of recommendation and endorsement ( 41 ) and exhibited restricted suitability in the context of reviews concerning conservation and environmental management.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, strict adherence to the PRISMA guidelines failed to detect any alterations in the journal’s level of recommendation and endorsement ( 41 ) and exhibited restricted suitability in the context of reviews concerning conservation and environmental management. Instead, the methodology selected in the present study was that described by McLean and Navas Gonzalez ( 42 ), which has been reported as an efficient methodology in previous studies ( 18 , 39 , 43 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations